Factors Associated with the Presence of E.coli in Food: Literature Review - Mulyati, Sri; Mursid Raharjo; Nurjazuli (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: Escherichia coli is a gram-negative bacterium of normal flora of the human and animal digestive tracts, and is important in human digestion. These bacteria can live in the stool, and can cause health problems, such as: diarrhea, vomiting, and other digestive problems. E coli bacteria can be pathogenic if the number of bacteria in the digestive tract increases or is outside the intestine. Food Sanitation Efforts include supervision, protection, and improvement of hygiene and sanitation quality specifically for Ready-to-Eat Processed Foods. Food hygiene and sanitation quality supervision is carried out through: surveillance, laboratory tests, risk analysis, and/or follow-up recommendations. Protection of food hygiene and sanitation quality is carried out through: communication, information, and education; health checks of food handlers; use of personal protective equipment; and/or the development of appropriate technology. Improving the quality of food hygiene and sanitation is carried out through: communication, information, and education; and/or food processing technology engineering Objective: The purpose of this literature review is to find out the factors related to the presence of E.coli in food Method: The research method used is a literature study with a search method in a literature review, which searches for literature that is in accordance with relevant social media such as google scholar, garuda, e-journal in the field of diarrhea incidence. Search the literature as a reference from 2014-2024 and get 10 articles or journals that are relevant in the last 10 years. Results: The results of this literature review explain that factors related to the presence of e.coli in food in public places include: personal hygiene of food handlers, how to wash cutlery, PPE of food handlers are not paid attention to, poor food sanitation, food handlers do not pay attention to controlling environmental conditions from the handling of raw materials to the distribution process, the storage place of cutlery is not considered, and improper serving of food. Conclusion: The conclusion of this literature review article is that there are many factors related to the presence of e.coli in food in public places. And recommend to environmental health workers the need to socialize and supervise the hygiene and sanitation of traders in particular. To the general public to pay attention to the cleanliness of what will be consumed.